Usability testing of EatsUp®: mobile application for monitoring balanced dietary practices and active lifestyle among adolescents—a study in Jakarta, Indonesia - Erfi Prafiantini; Erfi Prafiantini; Erfi Prafiantini; Rina Agustina; Rina Agustina; Betty Purwandari; Dian Novita Chandra; Dian Novita Chandra; Dini Rahma Bintari; Fellatinnisa Zafira Rajwadini; Jihan Farhanah; Aryono Hendarto (Frontiers in Digital Health)
BackgroundAdolescence is a critical period for establishing lifelong health habits, yet many adopt unhealthy behaviors, leading to obesity and other non-communicable diseases. Mobile apps offer a promising platform for delivering health interventions through education. Usability testing is essential to ensure mobile app features align with adolescent preferences and promote sustained behavior change.MethodsWe conducted an experimental usability study from June to August 2024 in Jakarta, Indonesia targeting adolescents aged 15–18 who used the EatsUp® mobile application. Participants engaged with the app for seven consecutive days, completing daily tasks and a user experience questionnaire. User experience was assessed across six domains—Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty—using a 7-point Likert scale. Descriptive statistics were used to analyze the data, which were compared against established user experience benchmarks.ResultsA total of 30 high school students participated (mean ± SD age 16 ± 0.70 years), of whom 23 (76.7%) were female. Most participants (90.0%) used the EatsUp® application for at least seven consecutive days. The app received positive and high user experience ratings across all six parameters, with mean scores exceeding 0.8. Compared to the benchmark data from previous UEQ studies, the app ranked in the “Excellent” category (top 10%) for five parameters, while Perspicuity was rated as “Good” (top 25%).ConclusionThe EatsUp® app demonstrated strong usability, with an overall positive user experience. It ranked as “Excellent” in five user experience parameters except perspicuity, making it well-suited for adolescents. However, perspicuity needs improvement to enhance ease of use. Study limitations include a predominantly female sample from Jakarta-based schools, limiting generalizability. Future studies should include a more diverse population and explore features like gamification to enhance long-term engagement.